Improving Therapy of Pharmacoresistant Epilepsies: The Role of Fenfluramine - Dini, Gianluca; Tulli, Eleonora; Dell’Isola, Giovanni Battista; Mencaroni, Elisabetta; Di Cara, Giuseppe; Striano, Pasquale; Verrotti, Alberto (Frontiers in Pharmacology, 2022)
Epilepsy is among the most common neurological chronic disorders, with a prevalence of 0. 5 – 1%. Despite the introduction of new antiepileptic drugs during recent years, about one third of the epileptic population remain drug-resistant. Hence, especially in the pediatric population limited by different pharmacokinetics and pharmacodynamics and by ethical and regulatory issues it is needed to identify new therapeutic resources. New molecules initially used with other therapeutic indications, such as fenfluramine, are being considered for the treatment of pharmacoresistant epilepsies, including Dravet Syndrome (DS) and Lennox-Gastaut Syndrome (LGS). Drug-refractory seizures are a hallmark of both these conditions and their treatment remains a major challenge. Fenfluramine is an amphetamine derivative that was previously approved as a weight loss drug and later withdrawn when major cardiac adverse events were reported. However, a new role of fenfluramine has emerged in recent years. Indeed, fenfluramine has proved to be a promising antiepileptic drug with a favorable risk–benefit profile for the treatment of DS, LGS and possibly other drug-resistant epileptic syndromes. The mechanism by which fenfluramine provide an antiepileptic action is not fully understood but it seems to go beyond its pro-serotoninergic activity. This review aims to provide a comprehensive analysis of the literature, including ongoing trials, regarding the efficacy and safety of fenfluramine as adjunctive treatment of pharmacoresistant epilepsies.